Tinjauan Sistematis Pembelajaran Berbasis AR/VR dalam PPG untuk Penguatan Nilai Gotong Royong dan Kebhinnekaan Global - effendi, heri; Pebriyenni, Pebriyenni; Morelent, Yetty; Rahayu, Ade Riza; Anjela, Puput Mia; Aisyah, Siti (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The use of Augmented Reality (AR) and Virtual Reality (VR) technologies in education has opened new opportunities to enhance learning quality, including within the Teacher Professional Education Program (PPG). As part of the effort to prepare professional teachers who can integrate the values of the Pancasila Student Profile, the exploration of AR- and VR-based learning becomes increasingly relevant for strengthening the values of gotong royong (mutual cooperation) and global diversity. This study aims to analyze the existing literature on the application of AR and VR in PPG and their impact on reinforcing these values. The research employed a Systematic Literature Review (SLR) approach, reviewing 38 articles published between 2014 and 2024 in reputable journals indexed by Scopus, Sinta, Springer, IEEE Xplore, and Google Scholar, ensuring relevance to the technological developments of the past decade. The findings indicate that AR and VR can create immersive learning environments that allow PPG participants to deeply understand cultural diversity and collaborate effectively through interactive simulations. Moreover, these technologies assist teachers in developing pedagogical competencies that support cross-cultural and project-based learning. Despite their great potential, the adoption of AR and VR remains constrained by issues of accessibility, cost, and the need for intensive teacher training. In conclusion, AR and VR make a significant contribution to promoting the values of gotong royong and global diversity within PPG; however, more inclusive and sustainable implementation strategies are required to maximize their educational impact.